FUNCTIONAL-SEMANTIC FEATURES OF INSTRUCTIONAL SEGMENTS IN ENGLISH AND UZBEK MEDICAL TEXTS - BATIROVA, Khurshida Egamberdiyevna (The Lingua Spectrum, 2025)
Instructional segments in medical texts are essential for guiding patients and healthcare professionals. This study examines the functional-semantic features of instructional segments in English medical texts and their Uzbek translations. The analysis is grounded in systemic-functional linguistics, corpus linguistics, and translation studies. Semantic modality, terminology, phrasal units, and cohesive devices are analyzed to determine how instructional meaning is preserved in translation. Findings demonstrate that instructional segments retain semantic fidelity, clarity, and directive force, ensuring effective communication in medical contexts.